THE ORGANISATION OF DISTANCE ENGLISH TEACHING TO FUTURE LAWYERS DURING THE WAR PERIOD - Bykonia Oksana; Shenderuk Olena; Borysenko Iryna; Ihnatovych Tetiana (Alfred Nobel University Publisher, 2022)
The authors of the article substantiate the peculiarities of organizing the distance teaching English to future lawyers with the use of a multimedia textbook during the war period. The aim of the article is to develop the conceptual foundations in the organization of future lawyers' distance learning of English with the use of a multimedia textbook during the war period. The tasks of the study are to cover theoretical background and to develop the foundations in the organization of future lawyers' distance learning of English with the use of a multimedia textbook during the war period. According to the aim and tasks of the study, it is proposed to carry out future lawyers' distance learning of English with the use of a multimedia textbook during the war period on the basis of personal-activity, competent and reflexive approaches. Research methods include theoretical methods (analysis of domestic and foreign resources on the theme of this research, analysis of modern programmes for teaching English for Specific Purposes and the Council Recommendation on a comprehensive approach to teaching and learning languages; the experience in forming English communicative competence to improve the effectiveness of teaching and learning English; analysis of online platforms for forming English communicative competence); empirical ones (testing of cadets and students to determine their level of formation of English communicative competence and the requirements of the programme for teaching foreign languages in a higher education institution; identifying the difficulties to improve the process of organizing the distance teaching English to future lawyers with the use of a multimedia textbook during the war period). The educational material of distance teaching English to future lawyers includes English speech and language samples, grammar rules, vocabulary of the topics for a certain stage of studying English at the Academy. The results of the study consist of the development of conceptual foundations in the organization of future lawyers' distance learning of English with the use of a multimedia textbook during the war period. The authors found that current events in Ukraine require essential modernization of the process of training future lawyers, first and foremost, to develop in them analytical changes, strategic thinking, the ability to synthesize information received through English mass media, use professional knowledge during communicating in English with foreign colleagues, quickly adapt to changes, etc. It was established that thanks to the integration of verbal and audiovisual information in the multimedia guide, the educational material on the chapter's topic is much better perceived and easier to remember for students, in addition, it is presented multi-level and varied. The developed technology of distance learning of English consists of the preparatory, organizational and final parts and organizational, educational and control stages. The authors propose to carry out distance learning of English using a multimedia guide on the basis of personally-oriented, competency-based and reflective approaches.